#TITLE_ALTERNATIVE# - FERDINAN AGOSTO (NIM 12203010); Pembimbing: Dr. Ir. Arsegianto M.Sc., HERRY
Any development plan of oil and gas field will face uncertainty in determining reserve and optimum reservoir production scenario. Therefore, a study for determining reservoir performance under recovery factor and the economical value parameter is necessary to be conducted. The objective of this paper study is to evaluate the result of reservoir performance forecasting and the economical value of the field by adding a number of optimum production well scenario. Plan of development is planned by adding a number of new production well to get the optimum number of well. The economical value of the field is determined by comparing Net Present Value (NPV) parameter from adding a number of optimum production well. The results of this paper study are an updated reservoir model and more accurate reservoir performance forecasting according to the recovery factor by optimizing number of well and the economical value of the field.